0838 Should Habitual Sleep Duration Be Added to The American Heart Association's "Life's Simple 7?". (12th April 2019) - Fourte, D Alex; Patterson, Freda; Malhotra, Atul; Seixas, Azizi; Killgore, William D S; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: The American Heart Association (AHA) suggests "Life's Simple 7" guidelines to improve overall health. The aim of this study was to test the hypothesis that sleep duration would be associated with each of the Simple 7 metrics and would provide additional information to overall health over and above that of the Simple-7. Methods: Data were from the 2011-2014 NHANES (N=8, 113). Habitual sleep duration was assessed by self-report and divided into very short(≤4h), short(5-6h), normal(7-8h) and long(≥9h). Overall health was self-rated as "Good" or "Poor." The components of the Simple-7 were assessed as high blood pressure (history, hypertensive medications, or ≥140/90mmHg), high cholesterol (history, statin use, or ≥240mg/dl), diabetes (history or fasting glucose ≥100mg/dl), unhealthy diet (fast food ≥7 meals in past week), obesity (BMI≥30kg/m2), inactivity (<30mins/day moderate/vigorous), and smoking (current). Covariates included age, sex, education, race/ethnicity and (in analyses without obesity) BMI. Results: In logistic regression analyses, poor overall health was associated with very short (OR=3.0, P<0.0005), short (OR=1.4, p<0.0005), and long (OR=1.7, p<0.0005) sleep. Variance explained for health by sleep (R-squared=0.02) was of similar magnitude to Simple-7 components (R-squared=0.0001[diet], 0.01[smoking, cholesterol), 0.02[obesity, sedentary], 0.04[hypertension, diabetes]). Sleep duration was associated with six of the Simple-7 (blood pressure, diabetes, diet, obesity, physical activity, and smoking). Sleep duration continues to be associated with overall health after controlling for all of the Simple-7 (very short OR=2.9, p<0.0005; short OR=1.3, p<0.0005; long OR=1.6, p<0.0005). Adding sleep to a model that contained covariates and the Simple-7 explained an additional 0.85% of the variance in health (retaining 46% of the variance explained in the outcome) without the Simple-7. Conclusion: Sleep is related to nearly all of the components of the Simple-7, is related to health even after accounting for the Simple-7, and explains variance in overall health above that explained by the Simple-7. These data/analyses suggest that a sleep assessment should be added to the Simple-7, given the observed increment in predictive value. Support (If Any): R01MD011600